(3cJGH aj GdHjYGJs
(3ChdgG (B:s
(3HjYI ehdGfG YeQ Hf GdNWGH HhjY YeQ QVj Gddg Yfg HhUjI CHj HcQ QVj Gddg Yfg HPdc ddfGS s
(3BNQgG (B:s
(3aeG RGdJ PG ZaQ Yf GdPfH de JRd JLhO hJYah efg hJcQekG s
(3Vef eLehY , JQJjHgG (B: (3ef U (B429 - (3U(B525s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B336 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs